Non-Thermal Plasma-Activated Water Enhances Nursery Production of Vegetables: A Species-Specific Study - Silvia Locatelli; Stefano Triolone; Marina De Bonis; Giampaolo Zanin; Carlo Nicoletto (Agronomy)
Non-thermal plasma technology (NTP) has found widespread applications across several fields, including agriculture. Researchers have explored the use of NTP to improve plant growth and increase agricultural product quality using plasma-activated water (PAW). This technology has shown potential benefits in boosting seed germination, promoting plant growth, as an effective defense against plant pathogens, and increasing systemic plant resistance. An experiment was set up over three different cultivation cycles to investigate the benefits of PAW administration on nursery production. Plasma-activated water was generated using two NTP intensities (PAW-HI = 600 mV; PAW-LI = 450 mV; CTR = tap water control) and manually applied to plants under greenhouse conditions. The species considered in the current study were tomato (Solanum lycopersicum L.), Swiss chard (Beta vulgaris L.), cabbage (Brassica oleracea L.), basil (Ocimum basilicum L.), and lettuce (Lactuca sativa L. var. Longifolia). The following morphological traits were measured at the end of each cycle and for each species: plant height (PH, cm), collar diameter (CD, mm), biomass (g), nutritional status (SPAD index), dry matter (DM, %), and chemical composition. The sturdiness index (SI) was determined by the PH-to-CD ratio. Results indicated a species-specific response to both PAW treatments compared to CTR. The plant height significantly increased in tomato (+11.9%) and cabbage (+5%) under PAW-HI treatment. In contrast, PAW-HI treatment negatively affected the PH in lettuce and basil (−18% and −9%, respectively). Swiss chard showed no significant response to either PAW-LI or PAW-HI treatments. Regarding DM, no significant differences were observed between the PAW treatments and CTR. However, an increase in total N content was detected in plant tissues across all species, except for basil, where no change was observed. The results suggest that PAW treatment has the potential to enhance vegetable nursery production, with species-specific responses observed in crops.